Transverse forced vibration of a diamond wire under support excitations. (1st January 2023) - Zheng, Jintao; Ge, Peiqi; Bi, Wenbo; Zhao, Yukang; Wang, Chao
Abstract: Diamond wire sawing is a key technology for wafer processing in the semiconductor industry. Transverse wire vibration decreases the wire web gap to below the critical adhesion spacing between the wires, which is an important factor that limits the development of diamond wire slicing technology toward narrower kerf losses and thinner as-cut wafers. In fact, the external excitation source that causes the diamond wire vibration comes primarily from the supports at both ends of the wire. Therefore, an analytic model for transverse forced vibration of a diamond wire under support excitations was developed in this study based on the transverse vibration theory of an axially-moving string fixed at both ends. This partial differential equation with non-homogeneous boundary conditions was solved using the superposition principle and the finite element method. To verify the theoretical model, experimental equipment to text the transverse vibration of a diamond wire with support excitations was developed. The support excitation signal and the wire vibration response were obtained using accelerometer measurements and machine vision detection, respectively. The theoretical results agree well with the experimental results, indicating the correctness of this proposed model. The effects of the vibration source and the installation parameters on the transverse vibration displacement of a diamond wire are discussed. The results show that hysteresis in the movement of the center of the wire causes a certain additional high-frequency vibration, which can make this maximum transverse displacement to be greater than the excitation amplitude, thus making the wire transverse vibration change non-linearly with some parameters. The maximum transverse vibration displacement at the center of the diamond wire increases with increases in the guide wheel machining error amplitude and the wire diameter as well as the wire span, while it decreases with increases in the wire groove diameter and the wire tension. This maximum transverse vibration displacement decreases by approximately 100.22 % and 6.17 % when the guide wheel manufacturing error amplitude and the wire groove diameter are reduced by half and doubled, respectively. Improving the manufacturing accuracy of the guide wheel is still the most effective way of reducing the transverse vibration displacement of the wire. In addition, appropriate increases in the groove diameter and the wire tension and decreases in the wire span are also beneficial for suppressing the wire vibration. Abstract : Image, graphical abstract